Kebijakan Hukum Dalam Menghadapi Lesbian, Gay, Biseksual dan Transgender (LGBT) Sebagai Suatu Penyimpangan Perilaku di Indonesia - I Putu Harry Suandana Putra (Warmadewa Press, 2024)
Deviant behavior in the form of Lesbian, Gay, Bisexual and Transgender (LGBT) seems unavoidable. This behavior can target children, teenagers and even adults. With this phenomenon, it has negative impacts on community life. The problem is getting stronger when the phenomenon is published through social media and television shows. At least there are perpetrators of LGBT couples and other LGBT actions in Indonesia. This study uses a research method that is a normative legal research type. In normative legal research, the data used is secondary data. The secondary data contains primary legal materials, secondary legal materials and tertiary legal materials. Then the materials that have been collected are analyzed using a statute approach and a case approach. This study answers a problem, namely first. The implications of LGBT behavioral deviations in Indonesia can have an impact on the health, social, education and security of the Indonesian state. The factors can be caused by internal factors originating from oneself and the family environment and external factors originating from the external environment and social media and television or community groups and second. In the provisions of the existing laws and regulations, there are limits for LGBT, although they are not regulated concretely and explicitly, and future regulations will regulate deviant behavior for LGBT groups who intentionally commit sexual harassment in public, but there is still a need for comprehensive regulations that regulate LGBT.